Aggressive behavior of Cutaneous squamous cell carcinoma in patients with chronic lymphocytic leukemia. (10th February 2014) - Tomaszewski, Jonathan M.; Gavriel, Haim; Link, Emma; Boodhun, Sholeh; Sizeland, Andrew; Corry, June
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Immunosuppression in organ transplant recipients increases the incidence and aggressiveness of cutaneous squamous cell carcinoma. However, there are little clinical data on cutaneous squamous cell carcinoma in patients with immunosuppression due to chronic lymphocytic leukemia. In this study we evaluated the clinical features, patterns of recurrence, and outcomes of cutaneous squamous cell carcinoma in patients with chronic lymphocytic leukemia. Study Design Retrospective cohort study. Methods A review was performed of 42 consecutive patients with cutaneous squamous cell carcinoma and chronic lymphocytic leukemia presenting to our institution between July 2000 and July 2010. Baseline characteristics, treatment details, and outcomes were analyzed. Results Thirty‐four patients presented with primary cutaneous squamous cell carcinoma (33 node negative, 1 node positive), and eight patients presented with nodal disease without a simultaneous index primary. The 2‐year cumulative incidence of local recurrence for primary cutaneous squamous cell carcinoma was 15%. Nodal recurrence occurred in 36% of node‐negative patients. The 3‐year overall and cause‐specific survival rate for all patients was 37% and 65%, respectively. In patients managed curatively for nodal disease at presentation or relapse (n = 17), the 3‐year overall and cause‐specific survival rate was 21% and 53%, respectively. Conclusions Patients with cutaneous squamous cell carcinoma and chronic lymphocytic leukemia experience higher rates of skin cancer recurrence and death than expected in an immunocompetent population. Novel strategies are needed to improve outcomes. Level of Evidence 4. Laryngoscope, 124:2043–2048, 2014